Distribution and Settling Regime of Transparent Exopolymer Particles (TEP) Potentially Associated With Bio‐Physical Processes in the Eastern Indian Ocean. Issue 4 (28th April 2021) - Guo, Congcong; Sun, Jun; Wang, Xingzhou; Jian, Shan; Abu Noman, Md.; Huang, Ke; Zhang, Guicheng
Abstract: The detailed transparent exopolymer particles (TEP) distribution, sinking behavior and the potential mechanisms behind that were revealed in the upper 200 m water column of the eastern Indian Ocean (EIO). The biological process and nutrient limitation have proved to be non‐negligible, both of which possessed potential functions in controlling the TEP pool. TEP production and fate presented significant subregional variations in the study area. The vertical distributions of TEP displayed coherent declined patterns with depth between the marginal sea and pelagic ecosystems, but the concentration of TEP horizontally decreased from marginal sea to open ocean. Dissimilarly, variable distribution patterns and magnitudes were distinguished between stratified and active current zones with the conclusion that the stratified condition was in favor of downward remove of TEP pool but turbulence facilitated the accumulation of TEP especially in the deep chlorophyll maximum (DCM) layer. Distinct sinking regimes of TEP in the stratified zone were distinguishable between layers, with the regulatory mechanisms in the upper, DCM and lower layer of water column being physical diffusion of denser seawater and solutes, aggregation by biotic and abiotic processes and buoyancy effect by entrained lighter fluid, respectively. By comparing the theoretical and measured sinking rates of TEP‐formed aggregates and considering the complicated and uncontrollable situations in non‐culture scenarios, the coupling effects of physical and biological variables on TEP dynamics were elucidated, thus providing a compelling theory for predicting the downward fate of carbon flux in the field environments. Plain Language Summary: Transparent exopolymer particles (TEP) have been brought into focus owing to their close relation with carbon cycle. However, the inconstant nature of TEP limits our understanding of TEP dynamic process, especially in situ. In this study, we measured TEP sinking rates onboard in the eastern Indian Ocean by recording the concentration variations between layers in the settling column after a given time. The fundamental purpose of this work was to expound the transport pattern of TEP above the 200 m‐depth water column ​in complicated field environment. We constructed a simplified model to emphatically discuss the functional mechanisms of physical diffusion and aggregation in the stratified environment. We also compared the measured sinking rates with the theatrical values by considering the varied properties of seawater and particles. The used measuring method for TEP sinking rates turned out to be receivable on one hand, and the model results helped explain the observed phenomena on the other hand. The changes of ambient variables as well as physical attributes of TEP were taken into account to draw a more integrated conclusion, which would provide a potential novel approach to figure out the carbon budget driven by TEP pool. Key Points: Transparent exopolymer particles (TEP) distribution and sinking dynamic were uncovered in non‐culture fields based on the model and statistical analysis methods The coupling of physical and biological factor has proved to be defining in controlling the production and fate of TEP The coordinated variation of TEP physical attributes tend to determine the ratio between the upward and downward flux of particulate organic carbon (POC)